2014
DOI: 10.1007/s10753-014-0007-y
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and Membrane-Stabilizing Properties of Two Semisynthetic Derivatives of Oleanolic Acid

Abstract: Acetylation and methylation semisynthesis of oleanolic acid (OA) isolated from Syzygium aromaticum L. yielded two compounds: 3-acetoxyoleanolic acid (3-AOA) and 3-acetoxy, 28-methylester oleanolic acid (3-A,28-MOA). Anti-inflammatory properties of these compounds were assessed using the serotonin and fresh egg albumin-induced inflammatory test models in male Wistar rats weighing 250-300 g. Furthermore, erythrocyte membrane-stabilizing property of these compounds was evaluated in the heat- and hypotonicity-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…Recently, OA was documented as a promising lead compound for new drug formulation [ 21 ]. Indeed, Habila et al [ 22 ] demonstrate the improvement of antibacterial effect of OA by decorating C 3 position hydroxy group with an acetyl group while Nkeh-Chungag et al [ 14 ] demonstrated improved analgesic and anti-inflammatory properties by semisynthesis of OA. The present study corroborates the fact that modification of OA in C 3 and C 28 positions results in enhancement of biological properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, OA was documented as a promising lead compound for new drug formulation [ 21 ]. Indeed, Habila et al [ 22 ] demonstrate the improvement of antibacterial effect of OA by decorating C 3 position hydroxy group with an acetyl group while Nkeh-Chungag et al [ 14 ] demonstrated improved analgesic and anti-inflammatory properties by semisynthesis of OA. The present study corroborates the fact that modification of OA in C 3 and C 28 positions results in enhancement of biological properties.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, several studies have been designed to modify the structure of OA with the hope of improving its physical properties for better bioavailability to enhance its bioactivity. Moreover, it is clearly demonstrated that the chemical structure of oleanolic acid has three “active” sites, the C 3 hydroxy, the C 12 to C 13 double bond, and the C 28 carboxylic acid [ 7 , 13 , 14 ], which may be chemically modified and thus change its physical and pharmacological effects.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al showed that OA could inhibit the generation of the inflammatory factors TNF- α and IL-6 [ 31 ]. Nkeh-Chungag et al found that OA exerted potent anti-inflammatory effects by inhibiting NO and PGE2 in RAW 264.7 cells [ 32 ]. Our results showed that OA decreased the levels of IL-6 and TNF- α in insulin-resistant HepG2 cells ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the past three decades, OA has been used in Chinese medicine for the treatment of liver disorders, including viral hepatitis. In vitro and in vivo studies have demonstrated that OA possesses potent antioxidant activities (15,16), and anti-inflammatory effects (17), which contribute toward its potential protective effects. However, whether OA exerts protective effects against renal I/R injury, and the possible underlying mechanism, Attenuation of renal ischemia/reperfusion injury by oleanolic acid preconditioning via its antioxidant, anti-inflammatory, and anti-apoptotic activities remain unclear.…”
Section: Introductionmentioning
confidence: 99%